53BP1 loss suppresses the radiosensitizing effect of icotinib hydrochloride in colorectal cancer cells. (7th March 2018) - Huang, Ai; Yao, Jing; Liu, Tao; Lin, Zhenyu; Zhang, Sheng; Zhang, Tao; Ma, Hong
Abstract: Background: This study aimed to investigate the influence of the expression of P53-binding protein 1 (53BP1), a key component in DNA damage repair pathways, on the radiosensitizing effect of icotinib hydrochloride in colorectal cancer and to elucidate the mechanisms underlying this influence. Materials and methods: Real-time RT-PCR and Western blotting were performed to verify the gene-knockout effect of 53BP1 small hairpin RNA (ShRNA), and colony formation assay was employed to investigate the influence of 53BP1 downregulation on the radiosensitizing effect of icotinib hydrochloride in HCT116 cells. Cell apoptosis, cell cycle distributions, and histone H2AX (γ-H2AX) fluorescence foci after 53BP1 knockdown were evaluated. Relative protein expression in the ataxia telangiectasia mutated kinase (ATM)-checkpoint kinase-2 (CHK2)-P53 pathway was measured by Western blot analysis to unravel the molecular mechanisms linking the pathway to the above phenomena. Results: Icotinib hydrochloride increased the radiosensitivity of HCT116 cells; however, this effect was suppressed by the downregulation of 53BP1 expression, a change that inhibited cell apoptosis, increased the percentage of HCT116 cells arrested in S-phase and inhibited the protein expression of key molecules in the ATM-CHK2-P53 apoptotic pathway. Conclusion: Our studies confirmed that the loss of 53BP1 serves as a negative regulator of the radiosensitizing effect of icotinib in part by suppressing the ATM-CHK2-P53 apoptotic pathway.